Cooperation between in-hospital psychological support and pastoral care providers: obstacles and opportunities for a modern approach. Issue 4 (August 2018) - Proserpio, Tullio; Ferrari, Andrea; Veneroni, Laura; Arice, Carmine; Massimino, Maura; Clerici, Carlo Alfredo
The meaning that patients with cancer attribute to life influences their expectations and their attitudes to the disease and its treatment. Over the centuries, religion has commonly been the answer encoded by the social setting when it came to matters of life and death. The present article analyzes the historical grounds for forms of cooperation between the scientific disciplines that focus on mental health and the approach of religion, centered on the Italian situation. Such cooperation was hard to imagine in the past, but the situation has changed considerably and cooperation is not only possible but extremely desirable. Acknowledgment of their spiritual needs helps patients to battle with their disease. The care of patients should include catering for their spiritual needs by ensuring the constant presence of a chaplain on hospital wards.